Kajian Kemampuan Adsorpsi Zeolit Alam Terimpregnasi Asam Lemak Hidroksamat sebagai Agen Pengkelat Ion Logam Tembaga - Muhsinun Muhsinun; Fena Prayunisa (Jurnal Kimia Fullerene, 2021)
One of the way to recycle heavy metals in the prevention of environmental pollution is by using a solid-liquid extraction method through the impregnation mechanism of chelating agent in the adsorbent to increase its ability to bind heavy metal ions. In this study, the impregnation of fatty hydroxamic acids (FHA) successfully carried out on active natural zeolite (ZAA). This is has been done to increase the maximum adsorption capacity of ZAA towards heavy metals. The purpose of this study was to examine the adsorption ability of FHA impregnated onto ZAA as a chelating agent in copper metal ions by using column chromatography. This column contains FHA, which synthesized from crude rice bran oil and impregnated onto ZAA. There are several parameters were investigated, they are, the effect of FHA concentration, mass of FHA-ZAA resin and pH of the metal ion sample. From this study, the concentration of FHA impregnated on the zeolite surface reached 41.60%. The optimum conditions for Cu(II) adsorption by FHA-ZAA were as follows: mass ratio of FHA-ZAA resin with Cu(II) concentration (g : ppm) was 1:100 and the optimum condition of Cu(II) ion was at pH 5.